Analgesic Efficacy of a New Immediate‐Release/Extended‐Release Formulation of Ibuprofen: Results From Single‐ and Multiple‐Dose Postsurgical Dental Pain Studies. Issue 3 (28th September 2016) - Christensen, Steven; Paluch, Ed; Jayawardena, Shyamalie; Daniels, Stephen; Meeves, Suzanne
Abstract: Analgesic effects of ibuprofen immediate‐release/extended‐release (IR/ER) 600‐mg tablets were evaluated in 2 randomized, double‐blind, placebo‐controlled dental pain studies. Patients 16–40 years old with moderate–severe pain following third‐molar extraction received single‐dose ibuprofen 600 mg IR/ER (formulation A or B), naproxen sodium 220 mg, or placebo (2:2:2:1; study 1) or 4 doses of ibuprofen 600 mg IR/ER (formulation A) or placebo (1:1; study 2). In study 1 (n = 196), mean (standard deviation [SD]) time‐weighted sum of pain intensity difference scores for placebo, ibuprofen IR/ER A, ibuprofen IR/ER B, and naproxen, respectively, were 0.05 (9.2), 16.87 (9.4), 17.34 (10.5), and 12.66 (10.0) over 0–12 hours and ‐0.03 (4.1), 6.57 (4.4), 7.14 (5.2), and 5.14 (5.0) over 8–12 hours (all P  < .001 vs placebo). In study 2 (n = 106), mean (SD) time‐weighted sum of pain relief and pain intensity difference scores were 18.2 (20.0) versus 41.5 (21.0) at 0–12 hours and 10.3 (12.0) versus 18.4 (12.1) at 8–12 hours for placebo versus ibuprofen IR/ER, respectively ( P  < .001 for both); efficacy was sustained over each of the four 12‐hour dosing intervals with ibuprofen. Gastrointestinal adverse events predominated with placebo both after study medication administration and after rescue medication use, if applicable. Ibuprofen 600 mg IR/ER provided safe and effective analgesia after single and multiple doses.